Periodontitis aggravates COPD through the activation of γδ T cell and M2 macrophage - Kaixin Xiong; Keping Ao; Wei Wei; Jiajia Dong; Jia Li; Yutao Yang; Boyu Tang; Yan Li (mSystems, 2024)
ABSTRACTChronic obstructive pulmonary disease (COPD) is a chronic systemic inflammatory disease with high morbidity and mortality. Periodontitis exacerbates COPD progression; however, the immune mechanisms by which periodontitis affects COPD remain unclear. Here, by constructing periodontitis and COPD mouse models, we demonstrated that periodontitis and COPD could mutually aggravate disease progression. For the first time, we found that the progression was associated with the activation of γδ T cells and M2 macrophages, and M2 polarization of macrophages was affected by γδ T cells activation. In the lung tissues of COPD with periodontitis, the activation of γδ T cells finally led to the increase of IL 17 and IFN γ expression and M2 macrophage polarization. Furthermore, we found that the periodontitis-associated bacteria Porphyromonas gingivalis (P. gingivalis) promoted the activation of γδ T cells and M2 macrophages ex vivo. The data from clinical bronchoalveolar lavage fluid (BALF) samples were consistent with the in vivo and ex vivo experiments. For the first time, our results identified the crucial role of γδ T-M2 immune mechanism in mediating periodontitis-promoted COPD progression. Therefore, targeting at periodontitis treatment and the γδ T-M2 immune mechanism might provide a new practical strategy for COPD prevention or control.IMPORTANCEPeriodontitis exacerbates chronic obstructive pulmonary disease (COPD) progression. For the first time, the current study identified that the impact of periodontitis on COPD progression was associated with the activation of γδ T cells and M2 macrophages and that M2 polarization of macrophages was affected by γδ T cells activation. The results indicated that targeting at periodontitis treatment and the γδ T-M2 immune mechanism might provide a new practical strategy for COPD prevention or control.